2010
DOI: 10.1111/j.1601-0825.2010.01774.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of myeloid cell leukemia‐1 by tolfenamic acid induces apoptosis in mucoepidermoid carcinoma

Abstract: These results suggest that Tol could be a potent anti-cancer drug for YD-15 MEC cells that acts by regulating the MCL-1 protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…2A). Previous studies showed that Mith, a drug that blocks expression of Sp1 and other Sp transcription factors inhibits Mcl-1 expression in mucoepidermoid carcinoma cells (Choi et al, 2011b), and results in Fig. 2, B and C, show that Mith also decreased expression of Mcl-1 protein and mRNA levels in HN22 and HSC4 cells.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…2A). Previous studies showed that Mith, a drug that blocks expression of Sp1 and other Sp transcription factors inhibits Mcl-1 expression in mucoepidermoid carcinoma cells (Choi et al, 2011b), and results in Fig. 2, B and C, show that Mith also decreased expression of Mcl-1 protein and mRNA levels in HN22 and HSC4 cells.…”
Section: Resultsmentioning
confidence: 79%
“…Recently, it has been reported that Mcl-1 is overexpressed in tumor cells of human primary OSCC and cultured SCC cell lines, suggesting that Mcl-1 may be an important drug target for treatment of human OSCC cases (Nagata et al, 2009). Our group also recently reported that downregulation of Mcl-1 by the non-steroidal anti-inflammatory drug (NSAID), tolfenamic acid induced apoptosis in YD-15 mucoepidermoid carcinoma cells, a major malignant carcinoma of the salivary gland (Choi et al, 2011b). However, these studies did not identify the molecular mechanisms and linkages between tolfeniamc s This article has supplemental material available at molpharm.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…To further strengthen the effect of LCA on Sp1, we scrutinized expression of Sp1 target proteins such as p21, p27, cyclin D1, Mcl-1 and survivin (9,33,34). The promoter of Sp1 target proteins contains frequent GC-rich sequences and can be regulated by Sp1 protein (35)(36)(37). Both p21 and p27, regulators of cell cycle progression (38,39), were dose-dependently increased when treated with LCA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that apicidin induced apoptosis and cell cycle arrest in ovarian, endometrial and breast cancer cells (8)(9)(10). Nevertheless, the precise molecular mechanism of cell death effect by apicidin remains unclear and, to the best of our knowledge, has not been previously examined in salivary mucoepidermoid carcinoma (MEC), the most common malignant salivary tumor corresponding to 34% of all salivary malignancies (11).…”
Section: Introductionmentioning
confidence: 99%